Pembuatan dan Karakterisasi Sifat Fisis Komposit Multilayer Serat Rami - Naila Hilmiyana Syifa; Agus Yulianto; Upik Nurbaiti (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2021)
The use of composites as an innovative new material is increasing. Composites are made from two or more materials that have different properties. This research was conducted to make multilayer composites and determine the effect of variations in the number of arrangements and the direction of the fiber angles on the physical properties of composites made from ramie fiber and epoxy. The physical properties of the composites analyzed in this study were density, porosity, water absorption, and thickness expansion. The composites in this study were made using the hand layup method with a volume fraction ratio of 30% and the ratio of epoxy and hardener was 2: 1. Before the composite was made, ramie fibers were soaked in 5% NaOH for 2 hours. This study succeeded in making epoxy ramie multilayer composites with variations in the number of arrangements and the direction of the fiber angles. Variations in the number of layers and the direction angle of the ramie fiber in the composite affect the density and porosity of the composite. Variations in the direction of the ramie fiber in the composite affect the water absorption of the composite. Variations in the number and direction of ramie fiber in the composite did not significantly affect the thickness of the composite.